Use patterns, knowledge diversity and drivers for the cultivation of the miracle plant [Synsepalum dulcificum (Schumach & Thonn.) Daniell] in Benin and Ghana - (:unkn) unknown (My University, 2021)
Source Agritrop Cirad (https://agritrop.cirad.fr/613611/) * Autres projets (id;sigle;titre): 2016–2988;MoBreed;(EU) Enhancing training and research mobility for novel crops breeding in Africa//
Keywords: African Research